A new species of Glyphis Ach. and three new records of Graphis Adans. (Graphidaceae) from Bali Island, Indonesia (Bangladesh Journal of Plant Taxonomy, 2018)
Glyphis batuana Hardini, Kasiamdari & Purnomo sp. nov. is a new species of lichenized fungus found on the bark of the Frangipani tree (Plumeria sp.). The new species from Batuan village (Gianyar districts), Bali Island, Indonesia is described and illustrated. It is characterized by its lirelliform, unbranched ascomata, entire labia, black, open disc with brown pruina, completely carbonized excipulum, 8-spored asci with 8-10 locular ascospores, and lack of secondary substances. A key to species of Glyphis Ach. in Indonesia is provided. Three new records of Graphis Adans., namely G. conferta Zenker, G. immersella Mull. Arg. and G. nilgiriensis Adaw. & Makhija are also reported.